Risk Sharing and Network Formation - Fafchamps, Marcel; Gubert, Flore (American Economic Review, 2007)
In this paper we examine whether risk sharing networks are formed so as to maximize the mutual gains from pooling income risk. The bene t from risk pooling is largest when households have different income pro les - e.g., different occupations - and are subjected to di¤erent sources of risk - e.g., live far apart. Gains from risk sharing therefore increase with social and geographical distance. But distance also raises the cost of interpersonal links. The net e¤ect on link formation is a priori indeterminate. We investigate this issue empirically using survey data from the rural Philippines.